Avaliação da durabilidade de concretos produzidos com agregados graúdos reciclados provenientes de cerâmicas vermelhas com diferentes taxas de pré-saturação - REIS, Felipe José Losada (Universidade Federal do Pará, 2015)
The amount of waste generated by the construction industry has been calling attention lately due to the size with which acts as the environmental impact of using non-renewable natural sources materials and increasing the amounts of waste produced by the urban environment. In Brazil, this estimate is around 90,000 tons generated per day. The proposed use of aggregate from CW ( construction waste ) as part of structural concrete becomes even more interesting from the moment we are seeking a reduction in costs for the production of concrete , carrying environmentalist mentality when sparing use of natural resources which some are already starting to run out. Banks of sand and pebble sources begin to fade due to the wide use of these aggregates in the concrete produced in Belém and inland cities in the state of Pará. The need for new sources of aggregates makes us seek in construction waste likely sources of aggregates responding in a similar fashion to natural. Considering this proposal, this dissertation evaluated the durability of concrete produced with the addition of ceramic CW through trials of water absorption by capillarity, carbonation, chloride ion penetration and electrical resistivity. To that end, we replaced the natural coarse aggregate by ceramic coarse aggregate by 50%, where this percentage of recycled aggregate was subjected to the rates of pre - saturation of 60 %, 80 % and 100 %. According to the results it can be seen that the presence of RCCA (recycled ceramic coarse aggregate), regardless of the degree of pre- saturation was significant in all the results, the fact that the concrete while leaving more susceptible to loss of durability, it showed a pattern of behavior in relation to the reference mixtures. The closest matches conventional concrete mixtures were made by containing pre- saturated with water at a rate of 80 % ceramic aggregates.